Association of sociodemographic and occupational stress factors with smoking behavior among healthcare professionals: The mediating role of physical exercise - Farooq A. Chaudhary; Asma Shakoor; Muhammad A. Fareed; Osama Khattak; Mohammed S. Alqarni; Rakhi Issrani; Thani Alsharari (Tobacco Induced Diseases)
Introduction Smoking remains a major preventable cause of mortality, posing a significant public health challenge globally. Healthcare professionals (HCPs), despite their pivotal role in promoting health, exhibit notable smoking behaviors influenced by occupational stress and sociodemographic factors. This study investigates these relationships and examines the mediating role of physical exercise in smoking behaviors among HCPs in Pakistan.